Operational Risk Assessment (ORA) for Local Government Engineering Department (LGED) in Bangladesh : Final Implementation Plan - World Bank (Washington, DC, 2013)
In April, 2008 the World Bank and the Local Government Engineering Department (LGED) commenced a study with the following objectives: (i) to assess fiduciary and operational risks in LGED's management of projects, assets and other resources, and in the Local Government Division (LGD), Ministry Of Local Government, Rural Development and Cooperatives' oversight function; (ii) to evaluate the efficacy of external review of decision-making by LGED and the LGD; and (iii) to identify options for future monitoring of operational risks in LGED and the LGD, and (iv) to prioritize options which are realistic and available to effectively minimize the major operational risks identified. This report addresses the last of these objectives. It is based on discussions in Dhaka 14-20 March with senior LGED staff the Operational Risk Assessment (ORA) team leader, and follow-up work by LGED staff through March 30. The report identifies and categorizes three different types of risks. The first type includes risks that LGED has the authority to take the necessary actions to address, with support from development partners and routine budgetary spending and staffing authorizations needed from other agencies. The second type includes risks that can only be addressed by LGED in partnership with one or more other organizations. In other words, it can initiate some parts, but will also need key partners to make necessary decisions to carry out the recommended actions. Although initial work on these can begin right away, successful implementation is expected to take longer than addressing the first type of risks. The third type includes risks that stem from the external environment in which LGED operates. LGED cannot take any direct action to address them. Yet, based on a full understanding of the nature of the risk, LGED may be able to take indirect actions to mitigate the relevant operational and fiduciary risks to LGED's operations and reputation. These are more complex than the first two types, and may take more time to address. Once finalized, the report will be presented and discussed at the ORA Dissemination Workshop tentatively scheduled for July, 2009, with participants from Government, civil society, and international partner organizations. Following approval by the Local Government Division, Ministry Of Local Government, Rural Development and Cooperatives, LGED will begin implementing the risk mitigating measures according to the attached schedule.